End‐stage renal disease incidence in a cohort of US firefighters from San Francisco, Chicago, and Philadelphia. Issue 12 (21st October 2022) - Pinkerton, Lynne E.; Bertke, Stephen; Dahm, Matthew M.; Kubale, Travis L.; Siegel, Miriam R.; Hales, Thomas R.; Yiin, James H.; Purdue, Mark P.; Beaumont, James J.; Daniels, Robert D.
Abstract: Background: Firefighters perform strenuous work in hot environments, which may increase their risk of chronic kidney disease. The purpose of this study was to evaluate the risk of end‐stage renal disease (ESRD) and types of ESRD among a cohort of US firefighters compared to the US general population, and to examine exposure–response relationships. Methods: ESRD from 1977 through 2014 was identified through linkage with Medicare data. ESRD incidence in the cohort compared to the US population was evaluated using life table analyses. Associations of all ESRD, systemic ESRD, hypertensive ESRD, and diabetic ESRD with exposure surrogates (exposed days, fire runs, and fire hours) were examined in Cox proportional hazards models adjusted for attained age (the time scale), race, birth date, fire department, and employment duration. Results: The incidence of all ESRD was less than expected (standardized incidence ratio (SIR) = 0.79; 95% confidence interval = 0.69–0.89, observed = 247). SIRs for ESRD types were not significantly increased. Positive associations of all ESRD, systemic ESRD, and hypertensive ESRD with exposed days were observed: however, 95% confidence intervals included one. Conclusions: We found little evidence of increased risk of ESRD among this cohort of firefighters. Limitations included the inability to evaluate exposure–response relationships for some ESRD types due to small observed numbers, the limitations of the surrogates of exposure, and the lack of information on more sensitive outcome measures for potential kidney effects.